La fiction urbaine contemporaine swahilie : quelques pistes - Ali Ryanga, Sheila; Wangari Maina, Rachel (Études littéraires africaines)

(untitled) (Association pour l'Étude des Littératures africaines (APELA), 2011)
Kenyan literary writers in Swahili soon after independence dwelt mostly with rural setting. Most of the works dwelt on African social values and philosophy within work ethics and relationships. However, with the growth of industries in urban centers, the issue of rural urban migration arose. Many educated Kenyans moved to urban centers in search of jobs. To mirror this change in society, literary writers enriched their works by using both the rural and urban settings. This became a constant feature in the works of literary writers in Swahili. Some of these features include street life, life in the slums and pollution. This paper attempts to study how the urban setting is depicted in modern Kenyan Swahili literary texts. Realism theory as propagated by both Georg Lukács and Bertolt Brecht will be invoked during the analysis of the texts, specifically, how the urban genre developed, images used to depict urban life and centers, and establish the influence of this genre on Swahili literary writing as a whole.